Qualification of a Surrogate Matrix-Based Absolute Quantification Method for Amyloid-β42 in Human Cerebrospinal Fluid Using 2D UPLC-Tandem Mass Spectrometry - Magdalena Korecka; Teresa Waligórska; Michal Figurski; Jon B. Toledo; Steven E. Arnold; Murray Grossman; John Q. Trojanowski; Leslie M. Shaw (2014)
The primary aims of this work were to: 1) establish a calibrator surrogate matrix for quantification of amyloid-β (Aβ)42 in human cerebrospinal fluid (CSF) and preparation of quality control samples for LC-MS-MS methodology, 2) validate analytical pe